2021
DOI: 10.3390/ijms22168768
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Otolaryngology: Focus on the Emerging Role of Estrogens in Inflammatory and Pro-Resolving Responses

Abstract: Otolaryngology (also known as ear, nose, and throat (ENT)) diseases can be significantly affected by the level of sex hormones, which indicates that sex differences affect the manifestation, pathophysiology, and outcomes of these diseases. Recently, increasing evidence has suggested that proinflammatory responses in ENT diseases are linked to the level of sex hormones. The sex hormone receptors are present on a wide variety of immune cells; therefore, it is evident that they play crucial roles in regulating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 232 publications
(375 reference statements)
0
8
0
Order By: Relevance
“…Females had greater odds of developing nasal polyps when low estradiol levels were present compared with normal levels 29 . Variations of gonadal hormones between males and females may contribute to the sex‐based differences seen in epidemiologic studies through inflammatory responses 30 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Females had greater odds of developing nasal polyps when low estradiol levels were present compared with normal levels 29 . Variations of gonadal hormones between males and females may contribute to the sex‐based differences seen in epidemiologic studies through inflammatory responses 30 …”
Section: Resultsmentioning
confidence: 99%
“…29 Variations of gonadal hormones between males and females may contribute to the sex-based differences seen in epidemiologic studies through inflammatory responses. 30…”
Section: Epidemiologymentioning
confidence: 99%
“…Therefore, the cells used in this study are only considered as different VFF cell lines, not as biologically female or male cells. Sex hormones play a role in ear, nose, and throat diseases [39]. While there are immunohistochemical studies showing the expression and distribution of estrogen and androgen receptors in human vocal folds [40][41][42], one study claims that these are unspecific staining patterns and thus false positives [43].…”
Section: Plos Onementioning
confidence: 99%
“…Sex differences in hearing loss have been discussed in relation to the protective effect of estrogen [31]. Increasing evidence has suggested that the proinflammatory response in otolaryngological diseases is linked to the level of sex hormones [32]. The vessels of female rats constrict less and relax more in response to adrenergic stimulation than do the vessels of males [33].…”
Section: Plos Onementioning
confidence: 99%